2015
DOI: 10.1002/pros.23000
|View full text |Cite
|
Sign up to set email alerts
|

Metformin represses androgen‐dependent and androgen‐independent prostate cancers by targeting androgen receptor

Abstract: Metformin represses prostate cancer cell viability and enhances apoptosis by targeting the AR signaling pathway. Combinations of metformin and other anti-AR agents pose a potentially promising therapeutic approach for treatment of prostate cancers, especially the castrate-resistant prostate cancer, with high efficacy and low toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 23 publications
6
65
1
Order By: Relevance
“…21 Previous studies demonstrated that metformin restrained prostate cancer cell proliferation, migration, and invasion and enhanced apoptosis. 13,22 These findings are consistent with our results. In contrast, Miyoshi et al suggested that metformin inhibited the growth of hepatoma cells by inducing G1 cell cycle arrest.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…21 Previous studies demonstrated that metformin restrained prostate cancer cell proliferation, migration, and invasion and enhanced apoptosis. 13,22 These findings are consistent with our results. In contrast, Miyoshi et al suggested that metformin inhibited the growth of hepatoma cells by inducing G1 cell cycle arrest.…”
Section: Discussionsupporting
confidence: 93%
“…Besides its main molecular target, AMPK, metformin also directly inhibits the mTOR pathway, 11 lipogenesis, 12 and the androgen receptor signaling pathway. 13 Nevertheless, the molecular mechanisms underlying these beneficial effects in prostate cancer remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Metformin, a potential anticancer agent, has been shown to inhibit growth and induce apoptosis though AMPK-dependent and -independent signaling pathways in CRPC cells5556. One study found that combination of metformin with other therapeutic agents, such as anti-AR agent bicalutamide, enhanced the growth inhibition of CRPC via AR-mediated signaling57. While metformin has been shown to inhibit NF-κB signaling in several other studies5859, the regulation of metformin to MUC1 signaling remains elusive60.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that persistent AR signalling remains the key driver in the progression to CRPC, and AR down-regulation is considered a preventive strategy for prostate cancer [63]. Metformin has been shown to reduce AR protein levels in a dose-dependent manner in androgen receptor-positive cell lines [49], and repress the AR signalling pathway via down-regulation of AR mRNA [64], again supporting a potential role for metformin in combination with ADT therapy.…”
Section: Biological Effectsmentioning
confidence: 99%